KEDUDUKAN HARTA BAWAAN DALAM PERKAWINAN YANG DISITAAKIBAT TINDAK PIDANA KORUPSI STUDI KASUS PUTUSAN MAHKAMAH AGUNG NOMOR 1948K/PDT/2015 - Melinda Ijaya; Hanafi Tanawijaya (Jurnal Hukum Adigama, 2022)
Confiscation of innate property in a marriage that occurs as result of criminal act ofcorruption committed by the husband, where the object confiscated is in the form of land obtainednot from the proceeds of a criminal act of corruption but from the gift of the wife's parents beforethe marriage. The research with the title "The Position of Congenital Assets Confiscated Due tothe Crime of Corruption is listed in the Supreme Court Decision Number 1948K/Pdt/2015"coreproblems, namely how the judge's consideration in determining the confiscation assets in marriageas a result of criminal acts of corruption, and how the position of innate property in a marriagerelated to the confiscation of a criminal act of corruption. The purpose of this study was todetermine the position of the innate assets confiscated by the state when there was a criminalconfiscation of corruption related to the corruption case that ensnared the husband, on the objectof land where the land was obtained from a parental grant from the wife long before the husband'scorruption and to find out how the judge's considerations in determine the confiscation ofcollateral in the husband's corruption crime. Based on the results of the research, it shows thatthere are legal irregularities where it is stated that the opponent has no interest in this case, wherein fact the opponent has an interest as the injured party. is not the result of a criminal act ofcorruption by the husband of the opponent.